All‐Angle Invisibility Cloaking of Contact Fingers on Solar Cells by Refractive Free‐Form Surfaces. Issue 17 (4th July 2017) - Schumann, Martin F.; Langenhorst, Malte; Smeets, Michael; Ding, Kaining; Paetzold, Ulrich W.; Wegener, Martin
Abstract : This work demonstrates a performance improvement of state‐of‐the‐art silicon solar cells by cloaking their metal contact fingers. The cloaking free‐form surfaces are fabricated on silicon heterojunction solar cells using direct laser writing of polymers and subsequent soft imprinting. Cloaking performance is determined experimentally by measuring spatially resolved and angle‐resolved current generation and the spectral response of the cell. The short‐circuit current density of the cell increases by 7.3%; its power‐conversion efficiency is enhanced by 9.3%. Overcompensation of the shadowing loss is found to be caused by improved light‐gathering and light‐trapping in the polymer layer. The experimental findings are in good agreement to ray‐tracing simulations. Abstract : Metallic contact grids reduce the efficiency of several types of solar cells by shading parts of their active area. The contact fingers of a prototypical silicon heterojunction solar cell are cloaked using a refractive free‐form surface. Increases in short‐circuit current density and power conversion efficiency are observed experimentally and found to be close to ray‐tracing simulation results.